Coherent all Optical Reservoir Computing for Equalization of Impairments in Coherent Fiber Optic Communication Systems - Shiva Kumar; Mahmoud M. T. Maghrabi; Mohamed H. Bakr; Toshihiko Hirooka; Masataka Nakazawa (IEEE Photonics Journal)
Reservoir computing (RC) is a bio-inspired framework suited for temporal data processing. Here we propose an all optical coherent RC for the equalization of the impairments of fiber optic (FO) system based on coherent detection. We compare the performances of the RC systems based on semiconductor saturable absorber mirror (SESAM) and highly nonlinear waveguide (HNLW). For a dispersion managed long haul FO system in which the nonlinear penalty is dominant, we find that the SESAM outperforms the HNLW due to its larger nonlinear memory. In contrast, for the equalization of dispersive impairments in a short haul FO system such as data center networks, we find that the HNLW has a much superior performance due to its larger linear memory.